PELATIHAN PENYUSUNAN CURRICULUM VITAE KREATIF DAN ATS FRIENDLY BAGI SISWA SMAN 5 DENPASAR - Helmy Syakh Alam; Anak Agung Gede Adi Mega Putra; Made Ayu Mira Maharani Arya Putri; I Kadek Damunas Mahesa Pratimana; Ni Made Ida Anggreni; I Made Lanang Marantika (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service activity aims to equip SMAN 5 Denpasar students with theoretical knowledge and practical skills in drafting professional Curriculum Vitae (CV), including creative and Applicant Tracking System (ATS) formats. Utilizing a Design Thinking approach and learning-by-doing methods, students participated in interactive workshops using Canva and Microsoft Word to transform academic achievements into professional documents. The results indicate a significant improvement in students' digital literacy, particularly regarding the technical mechanisms of automated recruitment systems, which were previously a major obstacle. This participatory approach proved effective in boosting students' confidence in identifying their potential and building competitive digital personal branding. Therefore, the training successfully bridged the gap between students' academic potential and modern industry standards, ensuring better preparedness for scholarship selections and the professional workforce.